In vivo quantification of proton exchange rate in healthy human brains with omega plot - Shaghaghi, Mehran; Chen, Weiwei; Scotti, Alessandro; Ye, Haiqi; Zhang, Yan; Zhu, Wenzhen; Cai, Kejia (Quantitative Imaging in Medicine and Surgery; Vol 9, No 10 (October 29, 2019): Quantitative Imaging in Medicine and Surgery (Chemical Exchange Saturation Transfer Imaging Special Issue), 2019)
Background: To implement omega plot method for in vivo mapping of proton exchange rates in human brain by taking into account the water direct saturation (DS) effect and multiple saturation transfer exchanging species in vivo. Methods: Four Z-spectra were collected with chemical exchange saturation transfer (CEST) saturation power =1, 2, 3 & 4 µT. Water DS was estimated by fitting the Z-spectrum to a linear combination of multiple Lorentzian components and its contribution to the signal was subsequently removed. Exchange rate maps were derived by the omega plot, consisting of fitting the inverse of the signal intensity, Mz/(M0−Mz), as a function of 1/(γB1)2. Results: The exchange rate values quantified with the DS removed omega plot were significantly higher in the GM region than in the WM region (616±29 vs. 575±20 s−1, P